Catálogo de las principales obras de la arquitectura revolucionaria en la ciudad de La Habana 1959 - 2009 - Domíguez Ruíz, Adriana (Universidad Central "Marta Abreu" de las Villas, 2010)
This paper presents a study of the architecture of the Cuban revolutionary period -from 1959 to 2009- in Havana city. As a result a catalog comprising 29 of the most outstanding building works is presented. It shows the value of the architectural works of the past fifty years. The subject is considered in three chapters: the first aims at explaining the concepts used in the research, as well as characteristics of the social-economic-historic-and-cultural situation in Cuba and in Latin America and their influence on the architecture; the second is devoted to analyzing the specific conditions that determine the architectural development in Havana city before and during the revolutionary period. To accomplish this task the Revolutionary period has been divided into five stages, each covering 10 years’ time: the first covers the period from 1959 to 1969, the second from 1970 to 1979, the third from 1980 to 1989, the forth from 1990 to 1999, and finally, from 2000 to 2009. Following the above order, we characterized and documented the architectural works that showed certain architectonic interest. To achieve this, a table was made so as to classify the most outstanding buildings found during the bibliographic search and field work. Finally in the third chapter the results of the research are presented, namely a catalog duly documented with an index of the selected architectural works. The index in question allows the identification of the works though a number of parameters such as the name of the building; its original intended location, as well as its present location. It also includes the date of inauguration, the name of the architects responsible for the work, an account of the original purpose the buildings were designed for and their actual use nowadays, graphic and photographic information about the original and present condition of the works, an integral evaluation of these, and lastly a reference to documents with an evaluation of the architectural works given by different authors.
Keywords: Catálogo de Obras; Arquitectura Revolucionaria; La Habana; Catalogs; Architecture